Embodyment Commedia Dell Arte of in Moliere Script: Cases Study with Le Medecin Malgre Lui - M Andreanda Dwi Putra; Saaduddin Saaduddin; Desi Susanti (Faculty of Languages and Arts, Universitas Negeri Padang, 2024)
The play